Structural Failure Analysis of Building E ITERA Due to The Pounding Effect with Non-Linear Time History - Nugraha Bintang Wirawan; Siska Apriwelni (UIR Press, 2020)
[EN] Lampung, a province where Institut Teknologi Sumatera (ITERA) is located, is an area that has a high level of seismicity. This research takes a case study of the Building E ITERA which has a dilatation building concept. Due to dilatation, inter-buildings have the risk of collisions because of earthquake loads. The purpose of this study is to determine the value of joint displacement in adjacent buildings when given a dynamic load of Time History and determine whether the adjacent buildings experience a pounding effect. A Time History earthquake load data that has been matched with the Lampung region response spectrum by software is applied to the model of Building E. Building E is modeled according to the as built drawing data and the results of field checking. Structure is analyzed using software. The results of the study showed that the structure of the Building E which was loaded by Loma Prieta earthquake that has been matched would experience inter-building collisions. Further research using earthquake record data taken in areas within certain radius from ITERA is need to be conducted to obtain more accurate results.